DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION TEACHING MATERIALS BASED ON INTERACTIVE MULTIMEDIA WITH A SCIENTIFIC APPROACH TO CLASS IV STUDENTS OF ELEMENTARY SCHOOL - Mawardi, Zulela MS, Mohamad SyarifSumantri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study analyzed the feasibility and effectiveness of the product model material teaching Islamic Religious Education based on interactive multimedia with a scientific approach for fourth-grade elementary school students in West Jakarta. The research and development types of research by adapting the Borg & Gall model combined with the Dick & Carey learning development steps and the Lee & Owens model with modifications. The instrument used in this study was the test, interview, questionnaires, and documentation. The validity of the data was generated based on the validation of material experts, media experts and linguists, and teacher and student responses. The results from this study showed the validity test results from material experts; an average score of 4.6 was obtained in the very good category. The validity test results from media experts obtained an average value of 4.4 with a good category. The validity test results of linguists obtained an average value of 4.7 with a very good category. The results of the teachers’ responses showed an average of 4.6. The students’ responses in thesmall group try-out show an average value of 3.37 (very good), and the average score of the assessment in the significant group test (field group try-out) of 3.5 (very good). Based on the results of the t -test through the independent samples test, the value of Sig. (2-tailed) of 0.016 < 0.05, which indicated a difference in the average students learning outcomes between the experimental class using MMI-based Islamic Education teaching materials and the control class using PowerPoint media. The result concluded that Islamic Religious Education teaching materials based on Interactive Multimedia with a